2018
DOI: 10.1186/s41938-018-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some environmental conditions on stability and activity of Bacillus thuringiensis formulations against the cotton leaf worm, Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae)

Abstract: The entomopathogenic bacterium Bacillus thuringiensis (Bt) has been used in crop protection for the last 70 years; however, many environmental conditions affect its activity. The present study was directed to evaluate the influence of certain environmental conditions on stability and activity of Bt samples of the two commercial formulations (Dipel 2 × 6. 4% WP and Protecto 9.4% WP), when stored under accelerated hot storage, shelf, and outdoor storage. Photo degradation of the two formulations was studied in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(28 reference statements)
0
5
1
Order By: Relevance
“…According to different studies, it is suggested that the larger the protein size, the longest it persists: Cry4 (130 kDa)> Cry11 (70 kDa)> Cyt (28 kDa) (Tetreau et al 2012 andBen 2014). In this study, it was clear that all Bti extracts tested had a high storage stability, in contrast with findings of different studies reporting poor protein stability of endotoxins under storage periods, in which shelf life was often low and the viability of products did not exceed 2 years under ambient conditions (Moustafa et al 2018).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…According to different studies, it is suggested that the larger the protein size, the longest it persists: Cry4 (130 kDa)> Cry11 (70 kDa)> Cyt (28 kDa) (Tetreau et al 2012 andBen 2014). In this study, it was clear that all Bti extracts tested had a high storage stability, in contrast with findings of different studies reporting poor protein stability of endotoxins under storage periods, in which shelf life was often low and the viability of products did not exceed 2 years under ambient conditions (Moustafa et al 2018).…”
Section: Discussioncontrasting
confidence: 45%
“…All this can produce conformational changes in its structure (Hung et al 2016), thus hinder toxic activity. However, there are some reports highlighting UV light and sunlight as a primary degradation pathway (Hung et al 2016;Moustafa et al 2018). Further research is needed to understand the role that this disaccharide could have in moderately conserving the activity and viability of the larvicidal proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, modification of the target site could lead to insensitivity of insect pests to insecticides [ 55 ]. In addition, factors such as UV light, sunlight, photolysis in water and shelf life could affect the insecticide efficiency and delay the development of the resistance/prevent it from occurring [ 56 ]. Thus, we speculate that the inconsistency with other studies might be due to the different species of insect, type of insecticide, time of sampling or method of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is inexpensive and practically can be propagated by the farmers. Unfortunately, this bacterium is sensitive and easily degraded by climatic factors (Abbaszadeh et al 2011;Moustafa et al 2018;Van Bokhorst-van de Veen et al 2015), for example, by ultraviolet sunlight. Ultraviolet is the main cause of cry toxin degradations (Pan et al 2017).…”
Section: Introductionmentioning
confidence: 99%